1999
DOI: 10.1021/jp992015t
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cu2+ Hydration and the Jahn−Teller Effect in Solution by QM/MM Monte Carlo Simulations

Abstract: The Cu2+ hydration shell structure has been studied by a combined ab initio quantum mechanical/molecular mechanical (QM/MM) Monte Carlo simulation, in which the ion and its first hydration sphere are treated at the Born−Oppenheimer ab initio quantum mechanical level, while classical pair and three-body potentials are employed for the remaining system. Whereas traditional simulations based on MM potentials are not able to predict higher-body effects such as the Jahn−Teller (JT) distorted octahedral structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 81 publications
4
59
0
Order By: Relevance
“…This effect is more dominant than in a previous QM/ MM MC simulation (see Table 3), [12] which had supplied a similar distance for the first peak (2.08 ä) but a smaller distance for the second one (4.2 ä). The smaller shift of the second hydration shell to larger Cu-O distances in the QM/MM simulation proves the influence of the different ligand arrangement in the QMtreated first hydration shell on the second shell.…”
Section: Structurementioning
confidence: 55%
See 3 more Smart Citations
“…This effect is more dominant than in a previous QM/ MM MC simulation (see Table 3), [12] which had supplied a similar distance for the first peak (2.08 ä) but a smaller distance for the second one (4.2 ä). The smaller shift of the second hydration shell to larger Cu-O distances in the QM/MM simulation proves the influence of the different ligand arrangement in the QMtreated first hydration shell on the second shell.…”
Section: Structurementioning
confidence: 55%
“…[12,48] It has been shown that nonadditivity plays a significant role for an accurate description of more subtle solvent effects. This is in agreement with our simulation results which clearly demonstrate that the description of the system with classical potentials is not adequate.…”
Section: Structurementioning
confidence: 99%
See 2 more Smart Citations
“…An important issue that arises in simulating liquid-state phenomena and diffusion through solids is the adaptive movement of the quantum mechanical region, which is called the "hot spot" [50,77,116,178]. Algorithms have been reported for liquid-phase simulation that allows water molecules to enter and leave the QM region dynamically.…”
Section: Adaptive Qm/mmmentioning
confidence: 99%